2017
DOI: 10.3390/biology6030033
|View full text |Cite
|
Sign up to set email alerts
|

Seed Coating with Hydro-Absorbers as Potential Mitigation of Early Season Drought in Sorghum (Sorghum bicolor L. Moench)

Abstract: Climate change poses a threat to sorghum production systems by shifting the onset of the rainy season to a later date, increasing the risk of crop failure during crop establishment. The effects of drought on sorghum during seedling establishment have not been determined. Coating seeds with a water absorbing substance offers a way to buffer the seed against insufficient moisture in the surrounding soil. Seeds of two different sorghum varieties were coated with one of two commercially available hydro-absorbers: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…The overall average values could have been distorted by the different responses of respective plant species to the coating technology. This is confirmed also by Vymyslický et al [ 34 ] or Gorim and Asch et al [ 33 ], who pointed out the effect of varieties that may influence the response to seed coating within one plant species. On the other hand, seed coating is considered a practice intended rather to improve handling and protection of plants (against mechanical or biological damage) and to a lesser extent also to enhance germination capacity [ 35 ].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The overall average values could have been distorted by the different responses of respective plant species to the coating technology. This is confirmed also by Vymyslický et al [ 34 ] or Gorim and Asch et al [ 33 ], who pointed out the effect of varieties that may influence the response to seed coating within one plant species. On the other hand, seed coating is considered a practice intended rather to improve handling and protection of plants (against mechanical or biological damage) and to a lesser extent also to enhance germination capacity [ 35 ].…”
Section: Resultssupporting
confidence: 71%
“…In the submitted study, no positive influence of coating was observed on the overall average values of seed drought resistance at higher PEG concentrations. The coating of seed with hydro-absorbents has been tested over a long time with respect to their influence on the growth of plants after sowing, i.e., their effect on the emergence of plants [ 33 ]. The coating of seed with a substance that is capable of binding water is considered a possibility for mitigating the impact of drought on the emergence of seed stock [ 8 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, seed coating with super absorbent polymer improved the energy and rate of seed germination, along with promoting seedling growth [21]. A previous study also reported that the dydro-absorber coating increased seedling performance under water-limited conditions, particularly by enhancing root growth [22]. However, the existing materials with seed coating are chemical, and the majority of them have little effect on seed vigor, germination characteristics, and seedling growth.…”
Section: Introductionmentioning
confidence: 99%